Arabidopsis thaliana mutants altered in homologous recombination - Masson, Jean E. (The National Academy of Sciences of the USA, 1997)
Homologous recombination contributes both to the generation of allelic diversity and to the preservation of genetic information. In plants, a lack of suitable experimental material has prevented studies of the regulatory and enzymatic aspects of recombination in somatic and meiotic cells. We have isolated nine Arabidopsis thaliana mutants hypersensitive to x-ray irradiation (xrs) and examined their recombination properties. For the three xrs loci described here, single recessive mutations were found to confer simultaneous hypersensitivities to the DNA-damaging chemicals mitomycin C (MMC(s)) and/or methyl methanesulfonate (MMS(s)) and alterations in homologous recombination. Mutant xrs9 (Xray(s), MMS(s)) is reduced in both somatic and meiotic recombination and resembles yeast mutants of the rad52 epistatic group. xrs11 (Xray(s), MMC(s)) is deficient in the x-ray-mediated stimulation of homologous recombination in somatic cells in a manner suggesting a specific signaling defect. xrs4 (Xray(s), MMS(s), MMC(s)) has a significant deficiency in somatic recombination, but this is accompanied by meiotic hyper-recombination. A corresponding phenotype has not been reported in other systems and thus this indicates a novel, plant-specific regulatory circuit linking mitotic and meiotic recombination.